2017
DOI: 10.1017/s000711451700071x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to vitamin D from fortified margarine and risk of fractures in late childhood: period and cohort results from 222 000 subjects in the D-tect observational study

Abstract: Prenatal low vitamin D may have consequences for bone health. By means of a nationwide mandatory vitamin D fortification programme, we examined the risk of fractures among 10–18-year-old children from proximate birth cohorts born around the date of the termination of the programme. For all subjects born in Denmark during 1983–1988, civil registration numbers were linked to the Danish National Patient Registry for incident and recurrent fractures occurring at ages 10–18 years. Multiplicative Poisson models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…In addition to the protocol paper [9], we have published 17 studies in the D-tect project on various outcomes. The primary outcomes were type 1 diabetes [10,11], birth weight and childhood obesity [12][13][14][15], and childhood fractures [16]. Secondary outcomes were gestational diabetes [17], pre-eclampsia [18,19], childhood asthma [20], adult celiac disease [21], inflammatory bowel disease [22], chance of live birth among women with fertility problems [23], and type 2 diabetes mellitus [24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the protocol paper [9], we have published 17 studies in the D-tect project on various outcomes. The primary outcomes were type 1 diabetes [10,11], birth weight and childhood obesity [12][13][14][15], and childhood fractures [16]. Secondary outcomes were gestational diabetes [17], pre-eclampsia [18,19], childhood asthma [20], adult celiac disease [21], inflammatory bowel disease [22], chance of live birth among women with fertility problems [23], and type 2 diabetes mellitus [24].…”
Section: Resultsmentioning
confidence: 99%
“…As already mentioned, the initial idea for the analyses in the D-tect fortification design studies was to compare the risk of selected chronic diseases in adjacent, as close as possible, exposed and unexposed birth cohorts, assuming that all other covariates or potential confounders would be equally distributed [9]. The discovery of the birth cohort effect documented for T1D cases for children born in Denmark around 1985 inspired us to look at different analytic approaches, and several of them were applied in subsequent studies: regression discontinuity [37] when analyzing T1D outcomes [10], age-period-cohort analyses [38] analyzing fracture outcomes [16], the approach similar to time series [39] analyzing birth weight seasonality [15]. For the latter outcome, the spectrum of the birth cohorts investigated was broad: slightly more than 50 years [15].…”
Section: Methodological Issues On Statistical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal diet and 25(OH)-vitamin D status during pregnancy might be associated with offspring bone development at birth and in childhood. However, the findings are inconsistent [4][5][6][7][8][9][10][11][12]. Maternal cigarette smoking might also have the ability to modulate bone mineral acquisition during intrauterine life [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that bone mineral content (BMC) in neonates differs by season of birth (Namgung & Tsang, 2003), and the risk for osteoporotic fractures in 60 to 70 year‐olds seems to be influenced by month of birth (Alffram, 1964). Some studies have found that children born in summer have more forearm fractures (Petersen et al, 2015), and that adults and adolescents born in winter have less hip and bone fractures (Abrahamsen, Heitmann, & Eiken, 2012; Handel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%